Суспільні передумови розвитку екотуризму в національних природних парках Волинської області - Міщенко, Олена Віталіївна; Mishchenko, Olena V. (Харківський національний університет імені В. Н. Каразіна, 2017)
Стаття присвячена дослідженню суспільних передумов розвитку екологічного туризму в національних природних парках Волинської області. Подано визначення поняття екологічний туризм, короткий аналіз попередніх досліджень з питань розвитку екологічного туризму в національних природних парках, методику оцінки суспільних ресурсів екотуристського потенціалу. Здійснена бальна оцінка за такими показниками: історико-культурна цінність, транспортна доступність, забезпеченість санаторно-курортними закладами. Проведено аналіз подієвих ресурсів та низки соціально-економічних показників – медичної та торгівельної мережі, закладів громадського харчування і розваг.

The article contains the definition of eco-tourism, a brief analysis of previous studies on the development of ecological tourism in national parks, the method of scoring public recreational resources. The assessment and analysis of the social preconditions of development of ecological tourism in national parks Volyn region is made basing on the parameters that determine the development of territorial recreational system. In the Volyn region created 3 national natural parks "Shatsky" "Pripyat Stokhid" Kivertsi "Puscha Tsumanska." However, public recreational resources within them are distributed quite unevenly, that caused the differences in the indexes of tourist flows and parks. The point valuation of recreational resources of public parks according to the index of historical and cultural value, transport accessibility, availability of health-resort institutions shows that the highest values (1.66 points) is fixed in Shatsky, medium - in "Pripyat Stokhid" (1.33 points), the lowest in Kivetsi and "Tsumanska Puscha" (1.00 points). The low rate of historical and cultural value parks of Volyn certainly can be compensated by the presence of unique natural resources. However, poor transport accessibility of the parks (Shatsky, Kivertsi "Tsumanska Puscha") and poor availability of health-resort institutions ("Pripyat Stokhid" Kivertsi "Tsumanska Puscha") significantly lowering the attractiveness of the recreational institution. The analysis of recreational infrastructure resources of investigated parks proved the availability of medical and commercial network, catering and entertainment. A positive aspect of the social component of the ecotourism potential of national parks of Volyn region is the presence of event resources. Thus, the international festival of extreme water tourism "Polesia Regatta" ("Pripyat Stokhid") and the song festival "On Svityaz waves" (Shatsky) are popular among Ukrainian and foreign tourists.
The public preconditions for the development of ecotourism in national parks of Volyn region
Keywords: екологічний туризм; національний природний парк; суспільні рекреаційні ресурси; історико-культурна цінність; транспортна доступність; забезпеченість санаторно-курортними закладами; eco-tourism; national park; public recreational resources; historical and cultural value; transport accessibility; availability of health-resort institutions